Business Model Canvas : The Bubble Entreprise ‘Hanger Dryer’ / Nur Aliya Shahirah A Hamid - A Hamid, Nur Aliya Shahirah (2020)
3 different category of customer that Bubble Sdn Bhd would like to focus. They are students, working people and also housewives. These group of people are considered due to many factors. When talked about hanger dryer, the main function is to hung clothes and drying. Thus, the group of people that involve with this activity are these 3 groups. The main reason is weather is something can be predicted but it is not 100% true. Therefore, people can be extra cautious but unexpected thing might happen. The sudden rain pour will lead to wet laundry. It some occasion they unable to return home to pick up the laundry. So in this conditions it is suggested to use hanger dryer. With regards to what have been stated above, I believe that these 3 groups of people are involved. Despite the fixed and busy schedule hanger dryer which can dry clothes within set time can provide a benefit to dry the laundry and ease the user